ESSENCE OF CIVIL-LEGAL MECHANISM OF ACQUISITION AND CESSATION OF MUNICIPAL PROPERTY RIGHT FOR LAND - N. N. Akhmadeyeva (Russian Journal of Economics and Law, 2013)
The article analyzes the legal nature, notion and signs of mechanism of acquisition and cessation of municipal property right for land; studies the correlation between notions “legal regulation” and “legal impact”; views the combination of private and public interest in civil-legal mechanism of acquisition and cessation of municipal property right for land.